2007
DOI: 10.1016/j.biocon.2006.10.051
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural intensification and loss of matrix habitat over 23 years in the West Wimmera, south-eastern Australia

Abstract: Agricultural intensification in south-eastern Australia -2 -Agricultural intensification and loss of matrix habitat over 23 years in the West Wimmera, south-eastern Australia AbstractThe global trend toward more intensive forms of agriculture is changing the nature of matrix habitat in agricultural areas. Removal of components of matrix habitat can affect native biota at the paddock and the landscape scale, particularly where intensification occurs over large areas. We identify the loss of paddock trees due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 30 publications
1
54
0
Order By: Relevance
“…This is the case, for example, when natural vegetation cover changes to cropland [72], when plot size increases [73], when irrigated cropland increases [35], or when the number of cropping cycles increases [34]. However, this study shows that when agricultural intensification manifests itself in land use system changes, an assessment at the landscape level may be better suited to capture these processes.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This is the case, for example, when natural vegetation cover changes to cropland [72], when plot size increases [73], when irrigated cropland increases [35], or when the number of cropping cycles increases [34]. However, this study shows that when agricultural intensification manifests itself in land use system changes, an assessment at the landscape level may be better suited to capture these processes.…”
Section: Discussionmentioning
confidence: 83%
“…More recently, scholars have begun to explore phenological profiles from Landsat time series, which has led to more accurate and more detailed cropland identification and change assessments [30][31][32]. Some studies have successfully assessed agricultural intensification in areas where it manifested itself in a change of land cover [33], a greater number of cropping cycles [34], or an increase in center-pivot irrigation areas [35]. However, most of these studies focus on pixel-level land cover and land use changes [32,36] rather than landscape-level changes towards more intense land use systems.…”
Section: Introductionmentioning
confidence: 99%
“…Interviews with farmers in our study area indicated that some of them planned to intensify their operations, using methods that would require clearing stepping stones to remove obstructions for the use of machinery (C. Gillies, unpublished data). Agricultural intensification in Australia, which also occurred to facilitate mechanization, resulted in the loss of up to 70% of stepping stones (Maron and Fitzsimons 2007). Furthermore, because the understory of these trees is now cattle pasture, some of which is regularly burned, new stepping stones do not appear to be recruiting to replace the loss of large trees.…”
Section: Discussionmentioning
confidence: 99%
“…In a drier future, adaptive risk management of an individual farming enterprise may include increased water security through larger dams on the property or by using ground water in pivot irrigation (Garnaut 2008). However, such individual risk management multiplied over many enterprises may increase the vulnerability of ecosystem function and services over the region, such as environmental flows and keystone remnant vegetation (Maron & Fitzsimmons 2007). In adaptation across landscapes, particularly those with a large percentage of private property, as in the NCCMA, individual risk mitigation action must be balanced with long-term landscape and social vulnerability and resilience (e,g, Ker 2010).…”
Section: Climate -Water -Irrigationmentioning
confidence: 99%